A nuclear grade high temperature ceramic refractory foam material and preparation method thereof

By combining modified hydroxyl-terminated polysiloxane and multivariate expansion flame retardant, the cohesion and flame retardant properties of refractory materials are improved, and the performance degradation of existing refractory materials under high temperature and corrosive media is solved, and the performance degradation of existing refractory materials in high temperature and corrosion media has been achieved. Stable sealing effect in nuclear power plant environment.

CN118638420BActive Publication Date: 2024-12-13YANTAI JINRUN NUCLEAR POWER MATERIAL CO LTD

Patent Information

Application Number
CN202411095334.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-13
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The existing refractory materials lack flame retardant performance in high-temperature environments and are sensitive to corrosive media, which can easily lead to performance degradation and powderization, affecting the sealing effect.

Method used

Using modified hydroxyl-terminated polysiloxane and multivariate expanded flame retardant, the cohesion and flame retardant properties of the material are improved through the synthesis of modified polysiloxane and multivariate expanded flame retardant, and through the modified polysiloxane The structure of the furan group and alkenyl group are introduced to enhance the compatibility and crosslinking activity of the material, combined with composite refractory fillers and glass powder to form a high-temperature ceramicized refractory foaming material.

Benefits of technology

It significantly improves the cohesion, flame retardant properties and corrosion resistance of the material, ensures stable performance in high temperature and corrosive media environments, extends service life, and meets the complex environmental needs of nuclear power plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118638420B_ABST
    Figure CN118638420B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, and discloses a nuclear-grade high-temperature ceramic refractory foaming material and a preparation method thereof; the nuclear-grade high-temperature ceramic refractory foaming material comprises the following raw materials: hydroxyl-terminated polysiloxane, modified polysiloxane, multinary expansion flame retardant, hydrogen-containing silicone oil, ethanol, composite refractory filler, methyl vinyl silicone resin, antioxidant, acetylene alcohol inhibitor, catalyst, glass powder, lithium carbonate and lithium oxide; the modified polysiloxane and multinary expansion flame retardant are prepared and added into the preparation process of the refractory foaming material, so that the prepared refractory foaming material has strong cohesion, is not prone to powdering during use, has good sealing performance, has excellent corrosion resistance and flame retardant effect, can meet the use requirements in the complex environment of a nuclear power plant, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a nuclear-grade high-temperature ceramic refractory foaming material and a preparation method thereof. Background Art

[0002] A nuclear power plant is a base station with radioactive materials and a large number of power equipment. Once a fire occurs, it will not only cause power outages but also may cause leakage of radioactive materials, resulting in casualties and environmental pollution. For the safety of nuclear power plant operation, fireproof sealing measures can effectively prevent the spread and diffusion of flames, heat and smoke in abnormal situations such as fire, thereby improving the overall fireproofing ability of the nuclear power plant. Refractory materials are a kind of sealing materials with strong fire resistance and are widely used in the field of fireproofing and sealing of nuclear power plants. In actual applications, due to the particularity of nuclear power plants, refractory materials are required to have not only excellent fire resistance, flame retardancy and fireproofing capabilities, and not be easy to powderize and fall off at high temperatures, but also good corrosion resistance. In the presence of corrosive media, they can still maintain stable performance and play a good role in fireproofing and sealing.

[0003] At present, ordinary refractory materials are difficult to meet the performance requirements of nuclear power plants, so they need to be improved in actual use. For example, the patent with announcement number CN110408276B discloses a cable incoming line fireproof sealing material, which is suitable for fireproof sealing of cable incoming lines in substations. It has the characteristics of high closed-pore rate, good temperature resistance, small compression deformation, excellent flame retardant and antistatic properties. However, the patent chooses to use inorganic material antimony trioxide as a flame retardant component, and its compatibility with organic matrix needs to be improved. There is a risk of weakened flame retardant ability when used in a long-term high-temperature environment. In addition, the fireproof sealing material has general corrosion resistance. The presence of corrosive media may lead to performance degradation, thereby affecting the sealing effect of the material and causing safety hazards. Summary of the invention

[0004] The purpose of the present invention is to provide a nuclear-grade high-temperature ceramic refractory foam material, which solves the following technical problems: (1) the performance of ordinary refractory foam materials decreases when used in an environment with corrosive media, affecting the sealing effect; (2) the flame retardant performance of ordinary refractory foam materials needs to be improved; (3) the cohesion of ordinary refractory foam materials is not strong, and they are easy to pulverize when used.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A nuclear-grade high-temperature ceramic refractory foaming material comprises the following raw materials in parts by weight: 40-60 parts of hydroxyl-terminated polysiloxane, 18-22 parts of modified polysiloxane, 2-5 parts of multi-component expansion flame retardant, 25-28 parts of hydrogenated silicone oil, 10-15 parts of ethanol, 6-7 parts of composite refractory filler, 12-15 parts of methyl vinyl silicone resin, 2-3 parts of antioxidant, 1-2 parts of acetylene alcohol inhibitor, 1-2 parts of catalyst, 2-5 parts of glass powder, 1-3 parts of lithium carbonate and 2-3 parts of lithium oxide.

[0007] Furthermore, the viscosity of the hydroxyl-terminated polysiloxane at room temperature is 5000-50000 Pa·s; and the hydrogen content of the hydrogen-containing silicone oil is 1.52-1.55%.

[0008] Furthermore, the composite refractory filler is zinc oxide, magnesium oxide and kaolin in a mass ratio of 1.2-1.5:2.8-3:2-2.5; the antioxidant is any one of antioxidant 1010, antioxidant 1076 and antioxidant 168; the alkynol inhibitor is any one of 3,7,11-trimethyldodec-1-yn-3-ol and 1-ethynyl-1-cyclohexanol; and the catalyst is a Custer catalyst.

[0009] Furthermore, the preparation method of the modified polysiloxane comprises the following steps:

[0010] S1: placing hydroxyl-terminated polysiloxane and glycidyl furfuryl ether in acetone, adding a promoter, heating to 50-55° C. for reaction for 3-5 hours, and collecting the product after removing the solvent by rotary evaporation to obtain furfuryl polysiloxane;

[0011] S2: Furfuryl polysiloxane and diallylcarbamoyl chloride are placed in dichloromethane, placed in an ice bath, triethylamine is added, and the mixture is stirred for 8-10 hours. The solvent is removed by vacuum distillation and the product is collected to obtain a modified polysiloxane.

[0012] Furthermore, in step S1, the dosage ratio of the hydroxyl-terminated polysiloxane, glycidyl furfuryl ether, acetone and accelerator is: 2-4g:2.5-3g:50-70ml:0.15-0.3g.

[0013] Furthermore, in step S1, the accelerator is aluminum chloride.

[0014] Furthermore, in step S2, the usage ratio of the furfuryl polysiloxane, diallylcarbamoyl chloride, dichloromethane and triethylamine is: 2.8-3.5g:2.5-3g:60-70ml:0.02-0.04g.

[0015] Furthermore, in step S2, the temperature of the ice bath is 0-4°C.

[0016] Through the above technical scheme, under the action of the accelerator, the hydroxyl group in the hydroxyl-terminated polysiloxane structure reacts with the epoxy group in the glycidyl furfuryl ether structure to obtain furfuryl polysiloxane, and then under the action of triethylamine, the hydroxyl group in the furfuryl polysiloxane structure reacts with the acyl chloride group in the diallylcarbamoyl chloride structure to obtain a modified polysiloxane. This modified polysiloxane has good compatibility with the base material, and has a furan group in its structure, which can effectively improve the corrosion resistance of the refractory foaming material, so that it can stably exist in the corrosive medium and expand its application field. At the same time, this polysiloxane structure has multiple alkenyl groups, which can provide more cross-linking active sites when preparing the refractory foaming material, improve the cohesion of the refractory foaming material, thereby effectively preventing the refractory foaming material from being powdered during use and affecting its sealing effect.

[0017] Furthermore, the preparation method of the multi-component expansion flame retardant comprises the following steps:

[0018] SS1: Place curdlan and 2-(1-imidazolyl)benzoic acid in dimethyl sulfoxide, fully stir and disperse, add p-toluenesulfonic acid, heat to 90-95°C for 6-8h, collect the product to obtain modified curdlan;

[0019] SS2: The modified curdlan, diphenyl chloromethyl phosphate and N,N-dimethylformamide are fully mixed, the temperature is raised and refluxed to react, and the product is collected after the reaction to obtain a multi-element intumescent flame retardant.

[0020] Furthermore, in step SS1, the usage ratio of the curdlan, 2-(1-imidazolyl)benzoic acid, dimethyl sulfoxide and p-toluenesulfonic acid is: 3-4 g: 3.5-4.5 g: 90-110 ml: 0.015-0.025 g.

[0021] Furthermore, in step SS2, the usage ratio of the modified curdlan, diphenyl chloromethyl phosphate and N,N-dimethylformamide is: 3.5-4g: 2.5-3.5g: 110-130ml.

[0022] Furthermore, in step SS2, the time of the temperature rising reflux reaction is 18-24h.

[0023] Through the above technical scheme, the hydroxyl group in the curdlan structure and the carboxyl group in the 2-(1-imidazolyl)benzoic acid structure undergo esterification reaction under the action of p-toluenesulfonic acid to obtain modified curdlan, and then the imidazole group in the modified curdlan structure reacts with the active chlorine in the diphenyl chloromethyl phosphate structure to obtain a multi-component expansion flame retardant. This multi-component expansion flame retardant uses curdlan as a carbon source, and after modification, an acid source and a gas source are introduced into its structure to form a multi-component expansion flame retardant system. When preparing refractory foam materials, only a small amount of addition is required to achieve an excellent flame retardant effect. When a fire occurs, the three play a synergistic role to form an expanded carbon foam layer covering the surface of the material, effectively improving the flame retardant ability of the refractory foam material.

[0024] A method for preparing a nuclear-grade high-temperature ceramic refractory foam material comprises the following steps:

[0025] Step 1: placing hydroxyl-terminated polysiloxane, modified polysiloxane, multi-component expansion flame retardant, hydrogen-containing silicone oil, ethanol, and composite refractory filler in a high-speed mixer, and stirring at 300-350 r / min for 1-1.5 h to obtain a first component mixture;

[0026] Step 2: Mix and grind the methyl vinyl silicone resin, antioxidant, acetylene alcohol inhibitor, catalyst, glass powder, lithium carbonate and lithium oxide for 0.5-1h to obtain a second component mixture;

[0027] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.5-2 hours, and then perform heat treatment to obtain a foamed material.

[0028] Furthermore, in step three, the heat treatment temperature is 80-90° C. and the time is 45-55 min.

[0029] Beneficial effects of the present invention:

[0030] The present invention prepares modified polysiloxane and adds a multi-element expansion flame retardant into the preparation process of the refractory foam material, so that the prepared refractory foam material has strong cohesion, is not prone to powdering during use, has good sealing performance, has excellent corrosion resistance and flame retardant effect, can meet the use requirements in the complex environment of a nuclear power plant, and has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1The zeta potential diagram of the curdlan, modified curdlan and multi-element expansion flame retardant of the present invention is shown in FIG. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The preparation methods of the modified polysiloxane and the multi-component expansion flame retardant in the following examples and comparative examples of the present invention are as follows:

[0035] 1. Preparation of modified polysiloxane

[0036] S1: 3 g of hydroxyl-terminated polysiloxane and 2.8 g of glycidyl furfuryl ether were placed in 60 ml of acetone, 0.2 g of aluminum chloride was added, the temperature was raised to 50° C. and reacted for 3 h, and the product was collected after the solvent was removed by rotary evaporation to obtain furfuryl polysiloxane;

[0037] S2: 3.2 g of furfuryl polysiloxane and 2.8 g of diallylcarbamoyl chloride were placed in 65 ml of dichloromethane, placed in an ice bath at 0°C, 0.03 g of triethylamine was added, and the mixture was stirred for 8 h. After the solvent was removed by vacuum distillation, the product was collected to obtain a modified polysiloxane.

[0038] The nitrogen element of furfuryl polysiloxane and modified polysiloxane was analyzed using vario EL cube element analyzer. The analysis showed that furfuryl polysiloxane did not contain nitrogen, and the nitrogen content of modified polysiloxane was 4.6%. The appearance of nitrogen in modified polysiloxane was due to the reaction between the hydroxyl group in the furfuryl polysiloxane structure and the acyl chloride group in the diallylcarbamoyl chloride structure, which introduced nitrogen into the furfuryl polysiloxane structure.

[0039] 2. Preparation of multi-element intumescent flame retardant

[0040] SS1: 3.5 g of curdlan and 4 g of 2-(1-imidazolyl)benzoic acid were placed in 100 ml of dimethyl sulfoxide, and after sufficient stirring and dispersion, 0.02 g of p-toluenesulfonic acid was added, and the temperature was raised to 90°C for reaction for 6 h, and the product was collected to obtain modified curdlan;

[0041] SS2: 3.8 g of modified curdlan, 3 g of diphenyl chloromethyl phosphate and 120 ml of N,N-dimethylformamide were fully mixed, and the mixture was heated to reflux for 18 h. After the reaction, the product was collected to obtain a multi-element intumescent flame retardant.

[0042] The potential values ​​of curdlan, modified curdlan and multi-element intumescent flame retardant were tested using JS94H zeta potential meter. Figure 1 It can be seen that the potential value of curdlan is -3.6mv; the potential value of modified curdlan is -0.7mv; the potential value of multi-intumescent flame retardant is 1.3mv; the potential values ​​of curdlan and modified curdlan are both negative, and the potential value of multi-intumescent flame retardant is positive. The change in positive and negative charges is due to the quaternization reaction between the imidazole group in the modified curdlan structure and the active chlorine in the diphenylchloromethyl phosphate structure to produce a positively charged quaternary ammonium group. Example 1

[0043] Preparation of foaming materials

[0044] Step 1: 40 g of hydroxyl-terminated polysiloxane with a viscosity of 5000 Pa·s, 18 g of modified polysiloxane, 2 g of multi-component expansion flame retardant, 25 g of hydrogen-containing silicone oil with a hydrogen content of 1.52%, 10 ml of ethanol, 1.2 g of zinc oxide, 2.8 g of magnesium oxide, and 2 g of kaolin are placed in a high-speed mixer and stirred at 300 r / min for 1 h to obtain a first component mixture;

[0045] Step 2: 12 g of methyl vinyl silicone resin, 2 g of antioxidant 1010, 1 g of 3,7,11-trimethyldodec-1-yn-3-ol, 1 g of Custer catalyst, 2 g of glass powder, 1 g of lithium carbonate and 2 g of lithium oxide were mixed and ground for 0.5 h to obtain a second component mixture;

[0046] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.5 hours, and then heat treat them at 80° C. for 45 minutes to obtain a foamed material. Example 2

[0047] Preparation of foaming materials

[0048] Step 1: 50 g of hydroxyl-terminated polysiloxane with a viscosity of 20000 Pa·s, 20 g of modified polysiloxane, 4 g of multi-component expansion flame retardant, 27 g of hydrogen-containing silicone oil with a hydrogen content of 1.53%, 13 ml of ethanol, 1.3 g of zinc oxide, 2.9 g of magnesium oxide, and 2.2 g of kaolin are placed in a high-speed mixer and stirred at 320 r / min for 1.2 h to obtain a first component mixture;

[0049] Step 2: 13 g of methyl vinyl silicone resin, 2.5 g of antioxidant 1076, 1.5 g of 1-ethynyl-1-cyclohexanol, 1.5 g of Custer catalyst, 3 g of glass powder, 2 g of lithium carbonate, and 2.5 g of lithium oxide were mixed and ground for 0.8 h to obtain a second component mixture;

[0050] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.8 hours, and then heat treat them at 85° C. for 50 minutes to obtain a foamed material. Example 3

[0051] Preparation of foaming materials

[0052] Step 1: 60 g of hydroxyl-terminated polysiloxane with a viscosity of 50,000 Pa·s, 22 g of modified polysiloxane, 5 g of multi-component expansion flame retardant, 28 g of hydrogen-containing silicone oil with a hydrogen content of 1.55%, 15 ml of ethanol, 1.5 g of zinc oxide, 3 g of magnesium oxide, and 2.5 g of kaolin are placed in a high-speed mixer and stirred at 350 r / min for 1.5 h to obtain a first component mixture;

[0053] Step 2: 15 g of methyl vinyl silicone resin, 3 g of antioxidant 168, 2 g of 1-ethynyl-1-cyclohexanol, 2 g of Custer catalyst, 5 g of glass powder, 3 g of lithium carbonate and 3 g of lithium oxide were mixed and ground for 1 hour to obtain a second component mixture;

[0054] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 2 hours, and then heat treat them at 90° C. for 55 minutes to obtain a foamed material.

[0055] Comparative Example 1

[0056] Preparation of foaming materials

[0057] Step 1, 50g of hydroxyl-terminated polysiloxane with a viscosity of 20000Pa·s, 20g of furfuryl polysiloxane, 4g of multi-component expansion flame retardant, 27g of hydrogen-containing silicone oil with a hydrogen content of 1.53%, 13ml of ethanol, 1.3g of zinc oxide, 2.9g of magnesium oxide, and 2.2g of kaolin are placed in a high-speed mixer, and stirred at 320r / min for 1.2h to obtain a first component mixture;

[0058] Step 2: 13 g of methyl vinyl silicone resin, 2.5 g of antioxidant 1076, 1.5 g of 1-ethynyl-1-cyclohexanol, 1.5 g of Custer catalyst, 3 g of glass powder, 2 g of lithium carbonate, and 2.5 g of lithium oxide were mixed and ground for 0.8 h to obtain a second component mixture;

[0059] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.8 hours, and then heat treat them at 85° C. for 50 minutes to obtain a foamed material.

[0060] Comparative Example 2

[0061] Preparation of foaming materials

[0062] Step 1, 50g of hydroxyl-terminated polysiloxane with a viscosity of 20000Pa·s, 20g of modified polysiloxane, 4g of diphenyl chloromethyl phosphate, 27g of hydrogen-containing silicone oil with a hydrogen content of 1.53%, 13ml of ethanol, 1.3g of zinc oxide, 2.9g of magnesium oxide, and 2.2g of kaolin are placed in a high-speed mixer, and stirred at 320r / min for 1.2h to obtain a first component mixture;

[0063] Step 2: 13 g of methyl vinyl silicone resin, 2.5 g of antioxidant 1076, 1.5 g of 1-ethynyl-1-cyclohexanol, 1.5 g of Custer catalyst, 3 g of glass powder, 2 g of lithium carbonate, and 2.5 g of lithium oxide were mixed and ground for 0.8 h to obtain a second component mixture;

[0064] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.8 hours, and then heat treat them at 85° C. for 50 minutes to obtain a foamed material.

[0065] Comparative Example 3

[0066] Preparation of foaming materials

[0067] Step 1: 70 g of hydroxyl-terminated polysiloxane with a viscosity of 20,000 Pa·s, 4 g of a multi-component expansion flame retardant, 27 g of a hydrogen-containing silicone oil with a hydrogen content of 1.53%, 13 ml of ethanol, 1.3 g of zinc oxide, 2.9 g of magnesium oxide, and 2.2 g of kaolin are placed in a high-speed mixer and stirred at 320 r / min for 1.2 h to obtain a first component mixture;

[0068] Step 2: 13 g of methyl vinyl silicone resin, 2.5 g of antioxidant 1076, 1.5 g of 1-ethynyl-1-cyclohexanol, 1.5 g of Custer catalyst, 3 g of glass powder, 2 g of lithium carbonate, and 2.5 g of lithium oxide were mixed and ground for 0.8 h to obtain a second component mixture;

[0069] Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.8 hours, and then heat treat them at 85° C. for 50 minutes to obtain a foamed material.

[0070] Performance Testing

[0071] The fire resistance and air tightness of the foamed materials prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were tested with reference to standard GB23864-2023; the samples were placed in a 10% by mass hydrochloric acid solution and a 10% by mass sodium hydroxide solution for 12 hours, and the samples were observed to see whether they swelled or cracked, and the corrosion resistance of the samples was determined; the flame retardant properties of the samples were tested with reference to the UL-94 standard; the samples were placed in an 80°C aging box for 24 hours, and the surface state of the samples was observed to see whether powdering occurred; the specific test results are shown in the table below:

[0072] Fire resistance integrity / h <![CDATA[Air tightness / m 3 / (m·h)]]> Acid corrosion resistance Alkali corrosion resistance Flame retardant grade Surface state Example 1 3.3 <3 No change No change V-0 No change Example 2 3.5 <3 No change No change V-0 No change Example 3 3.4 <3 No change No change V-0 No change Comparative Example 1 3.2 >3.5 No change No change V-0 Powdering Comparative Example 2 3.0 <3 No change No change V-1 No change Comparative Example 3 2.9 >3.5 Swelling and cracking Swelling and cracking V-0 Powdering

[0073] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent fire resistance, air tightness, corrosion resistance and flame retardant properties, good cohesion and are not easy to powderize and fall off, have a wide range of uses and a long service life. In the sample prepared in Comparative Example 1, furfuryl polysiloxane was added, and the corrosion resistance was strong but the cohesion was generally resulting in a general sealing effect and easy powdering. In the sample prepared in Comparative Example 2, diphenyl chloromethyl phosphate was added, and the flame retardant effect was not as good as that in the embodiment. This is because the multi-expansion flame retardant used in the embodiment only requires a small amount to achieve an excellent flame retardant effect, which is difficult to achieve using the same amount of diphenyl chloromethyl phosphate alone. In the sample prepared in Comparative Example 3, the modified polysiloxane was replaced with a hydroxy-terminated polysiloxane, and the corrosion resistance and cohesion were general, the material was easy to powderize, the service life was short and it was difficult to meet the use requirements of the environment when corrosive media were present.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0075] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A nuclear grade high temperature ceramic refractory foaming material, It is characterized in that The invention comprises the following raw materials in parts by weight: 40-60 parts of hydroxyl-terminated polysiloxane, 18-22 parts of modified polysiloxane, 2-5 parts of multi-component expansion flame retardant, 25-28 parts of hydrogenated silicone oil, 10-15 parts of ethanol, 6-7 parts of composite refractory filler, 12-15 parts of methyl vinyl silicone resin, 2-3 parts of antioxidant, 1-2 parts of acetylene alcohol inhibitor, 1-2 parts of catalyst, 2-5 parts of glass powder, 1-3 parts of lithium carbonate and 2-3 parts of lithium oxide; The preparation method of the multi-element expansion flame retardant comprises the following steps: SS1: Place curdlan and 2-(1-imidazolyl)benzoic acid in dimethyl sulfoxide, fully stir and disperse, add p-toluenesulfonic acid, heat to 90-95°C for 6-8h, collect the product to obtain modified curdlan; SS2: Fully mix the modified curdlan, diphenyl chloromethyl phosphate and N,N-dimethylformamide, heat up and reflux to react, collect the product after reaction, and obtain a multi-element intumescent flame retardant; The preparation method of the modified polysiloxane comprises the following steps: S1: placing hydroxyl-terminated polysiloxane and glycidyl furfuryl ether in acetone, adding a promoter, heating to 50-55° C. for reaction for 3-5 hours, and collecting the product after removing the solvent by rotary evaporation to obtain furfuryl polysiloxane; S2: Furfuryl polysiloxane and diallylcarbamoyl chloride are placed in dichloromethane, placed in an ice bath, triethylamine is added, and the mixture is stirred for 8-10 hours. The solvent is removed by vacuum distillation and the product is collected to obtain a modified polysiloxane.

2. A nuclear-grade high-temperature ceramic refractory foam material according to claim 1, It is characterized in that The viscosity of the hydroxyl-terminated polysiloxane at room temperature is 5000-50000 Pa·s; the hydrogen content of the hydrogen-containing silicone oil is 1.52-1.55%.

3. A nuclear-grade high-temperature ceramic refractory foam material according to claim 1, It is characterized in that The composite refractory filler is zinc oxide, magnesium oxide and kaolin in a mass ratio of 1.2-1.5:2.8-3:2-2.5; the antioxidant is any one of antioxidant 1010, antioxidant 1076 and antioxidant 168; the alkynol inhibitor is any one of 3,7,11-trimethyldodec-1-yn-3-ol and 1-ethynyl-1-cyclohexanol; and the catalyst is a Castel catalyst.

4. A nuclear-grade high-temperature ceramic refractory foam material according to claim 1, It is characterized in that In step S1, the accelerator is aluminum chloride.

5. A nuclear-grade high-temperature ceramic refractory foam material according to claim 1, It is characterized in that In step S2, the temperature of the ice bath is 0-4°C.

6. A nuclear-grade high-temperature ceramic refractory foam material according to claim 1, It is characterized in that In step SS2, the temperature rising and reflux reaction time is 18-24h.

7. A method for preparing the nuclear-grade high-temperature ceramic refractory foam material as claimed in claim 1, It is characterized in that The following steps are involved: Step 1: placing hydroxyl-terminated polysiloxane, modified polysiloxane, multi-component expansion flame retardant, hydrogen-containing silicone oil, ethanol, and composite refractory filler in a high-speed mixer, and stirring at 300-350 r / min for 1-1.5 h to obtain a first component mixture; Step 2: Mix and grind the methyl vinyl silicone resin, antioxidant, acetylene alcohol inhibitor, catalyst, glass powder, lithium carbonate and lithium oxide for 0.5-1h to obtain a second component mixture; Step 3: Evenly mix the first component mixed material and the second component mixed material, foam them at room temperature for 1.5-2 hours, and then perform heat treatment to obtain a foamed material.

8. A method for preparing a nuclear-grade high-temperature ceramic refractory foam material according to claim 7, It is characterized in that In step 3, the heat treatment temperature is 80-90°C and the time is 45-55 minutes.

Citation Information

Patent Citations

  • A material for fireproof sealing of cable inlets

    CN110408276B

  • Intrinsic flame-retardant transparent organic silicon fireproof coating and preparation method thereof

    CN113372747A

  • High-temperature-resistant halogen-free flame-retardant ceramic fireproof organic silicon foam material and preparation method thereof

    CN115260765A

  • Nuclear-grade high-temperature ceramic refractory foaming material and preparation method thereof

    CN116904031A

  • High-viscosity adhesive and production method thereof

    CN118374250A

Cited By

  • Novel efficient fire-resistant heat insulation plate for nuclear power and preparation method thereof

    CN122233748A